Knowledge, Attitude, and Willingness Toward Kidney Donation Among Health Sciences Students at King Saud Bin Abdulaziz University - Sharaan, Raghad; Alsulami, Sara; Arab, Raneem; Alzeair, Ghida; Elamin, Nadia; Alsaywid, Basim; Lytras, Miltiadis (Frontiers in Public Health, 2021)
Background: End-sd-stage renal disease, as one of the most serious and major health problems, does not have many treatment options available. One of the best treatment modalities used to cure this debilitating disease is kidney transplantation. However, with the continuous increase in number of patients diagnosed with it, there is not enough supply of the organ. The aim of our study is to assess knowledge about, attitude towards, and willingness to donate kidney among health science students at King Saud bin Abdulaziz University in comparison to the general population in Jeddah and investigating the factors that play a role on their willingness. Methods: This is an observational, analytical, cross-sectional study design conducted in 2019. Two target populations were included, King Saud bin Abdulaziz university for health sciences students and general population in Jeddah. Data was collected via self-administered, close-ended, structured, and previously validated questionnaire that contained 39 items divided in four sections. SPSS program version 22 was used in data analysis. Results: Out of 685 surveyed participants, 179 (26.1%) of them were willing to donate their kidney, with students showing higher rate of willingness 101 (32.3%) than the general population 78 (21%). However, only 46 (6.7%) out of the total population were holding an organ donor card. In bivariate analysis, it was found that knowledge significantly associated with higher rate of willingness among the student's population than the general population, while positive beliefs were associated with increased willingness in the general population than students. Positive attitude appeared to play a role in higher willingness among general population and student population respectively. Conclusion: There is low perception of awareness regarding kidney donation on this study populations. The willingness rate of health science students at king Saud bin Abdulaziz University and general population was low when compared with other studies conducted internationally.